Menguji Faktor Determinan Financial Sustainability pada Sektor Pemerintah - Dinar Tri Wardhani; Payamta Payamta (Universitas Swadaya Gunung Jati, 2020)
AbstractThis study aims to examine the factors that influence financial sustainability in government sector. The factors are chosen in terms of demographics, economics, social, and finance in the local government. The results of this study are important to be advice for district or city governments in Indonesia to make appropriate policies so that they can encourage financial sustainability without burdening the community. Financial sustainability is measured using elements in adjusted Operational Reports. The population of this study is the district / city government in Java on 2015-2018 fiscal year. The research sample was taken using the purposive sampling method, obtained a sample of 414 as research observations. Data analysis method used is panel data multiple regression analysis with Eviews version 10. The results of this study indicate that the population, and debt to income ratio negatively affect financial sustainability, financial independence has a positive effect on financial sustainability. Meanwhile gross regional domestic product and the human development index have no effect on financial sustainability in local governments.Keywords: Financial sustainability; Human development index; Financial independence; Local government; Debt to revenue ratioAbstrak Penelitian ini bertujuan untuk menguji faktor-faktor yang mempengaruhi financial sustainability di sektor pemerintah. Faktor-faktor tersebut dipilih dari segi demografi, ekonomi, sosial, dan keuangan pada pemerintah daerah. Hasil penelitian ini penting untuk menjadi masukan bagi pemerintah kabupaten atau kota di Indonesia dalam membuat kebijakan yang tepat sehingga dapat mendorong keberlanjutan keuangan tanpa membebani masyarakat. Financial sustainability diukur menggunakan unsur-unsur pada Laporan Operasional yang telah disesuaikan. Populasi penelitian ini adalah pemerintah daerah kabupaten/kota di Puau Jawa tahun anggaran 2015-2018. Sampel penelitian ini diambil menggunakan metode purposive sampling, diperoleh sampel sebanyak 414 pemerintah daerah. Metode analisis data yang digunakan adalah analisis regresi berganda data panel dengan bantuan program Eviews versi 10. Hasil penelitian ini menunjukkan bahwa jumlah penduduk, dan rasio hutang pada pendapatan berpengaruh negatif terhadap financial sustainability, kemandirian keuangan berpengaruh positif terhadap financial sustaianability. Sementara itu produk domestik regional bruto dan indeks pembangunan manusia tidak berpengaruh terhadap financial sustainability di pemerintah daerah.Katakunci: Financial sustainability; Indeks pembangunan manusia; Kemandirian keuangan; Pemerintah daerah; rasio hutang pada pendapatan